DEBUNKING THE MYTHS OF NON-NATIVE ENGLISH SPEAKER TEACHERS: AN INTERVIEW WITH PROFESSOR MASAKI - Floris, Flora Debora (TEFLIN Journal, 2016)
Masaki Oda is a Professor of Applied Linguistics at Tamagawa University in Tokyo, Japan, specializing in Sociopolitical Aspects of Language Use. Prof. Oda got his PhD program from Georgetown University, where he also taught Japanese for several years. He returned to Japan in 1990 and began teaching EFL and training EFL teachers at Tamagawa University. He was the 2003 – 2004 Chair of the NNEST Caucus and is now the Director of Center for English as a Lingua Franca (CELF) at Tamagawa University and the AsiaTEFL Vice President. This interview highlights Professor Oda’s experiences and opinions regarding NEST (Native English Speaker Teacher) and NNEST (Non-Native English Speaker Teacher). He attempts to raise awareness among the professionals that there should be no divide between NEST and NNEST in the ELT profession.